INVESTMENT PROFITABILITY ANALYSIS OF AN ON-GRID PHOTOVOLTAIC SYSTEM - Piotr Szpulak; Szczepan Paszkiel; Stanisław Wawrzyniak; Mirosław Gryszpiński (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The potential of the solar energy sector is starting to become increasingly important. The possibility to produce electrical power for household needs, as a result of an investment in photovoltaics is gaining popularity, and storing its surplus in a power grid and settlement of its consumption on the basis of an annual balance, allows to limit electricity bills to the minimum. The implementation stage, which promotes investing in solar renewable energy for own household needs was introduced by the new Act on RES, promoting the prosumer On-Grid system. The paper focuses on presenting the analysis of profitability of installing photovoltaic On-grid systems.